Analysis and performance assessment of a combined geothermal power-based hydrogen production and liquefaction system. (31st May 2018) - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim
Abstract: In this paper, the thermodynamic study of a combined geothermal power-based hydrogen generation and liquefaction system is investigated for performance assessment. Because hydrogen is the energy of future, the purpose of this study is to produce hydrogen in a clear way. The results of study can be helpful for decision makers in terms of the integrated system efficiency. The presented integrated hydrogen production and liquefaction system consists of a combined geothermal power system, a PEM electrolyzer, and a hydrogen liquefaction and storage system. The exergy destruction rates, exergy destruction ratios and exergetic performance values of presented integrated system and its subsystems are determined by using the balance equations for mass, energy, entropy, energy and exergy and evaluated their performances by means of energetic and exergetic efficiencies. In this regard, the impact of some design parameters and operating conditions on the hydrogen production and liquefaction and its exergy destruction rates and exergetic performances are investigated parametrically. According to these parametric analysis results, the most influential parameter affecting system exergy efficiency is found to be geothermal source temperature in such a way that as geothermal fluid temperature increases from 130 °C to 200 °C which results in an increase of exergy efficiency from 38% to 64%. Results also show that, PEM electrolyzer temperature is more effective than reference temperature. As PEM electrolyzer temperature increases from 60 °C to 85 °C, the hydrogen production efficiency increases from nearly 39% to 44%. Highlights: Geothermal energy based hydrogen production and liquefaction system is suggested. Exergy analysis and performance assessment of combined system components are given. Energetic and exergetic performance of combined system are investigated. Effects of design variables on power and hydrogen generation are investigated.